2022
DOI: 10.1038/s41598-022-21230-3
|View full text |Cite
|
Sign up to set email alerts
|

Minimal hepatic encephalopathy is associated to alterations in eye movements

Abstract: Minimal hepatic encephalopathy (MHE) is diagnosed using PHES battery, but other tests are more sensitive, and a simple tool for early MHE detection is required. Assessment of saccadic eye movements is useful for early detection of cognitive alterations in different pathologies. We characterized the alterations in saccadic eye movements in MHE patients, its relationship with cognitive alterations and its utility for MHE diagnosis. One-hundred and eighteen cirrhotic patients (86 without and 32 with MHE) and 35 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is worth noting that palsies of the 3rd, 4th, and 6th cranial nerve are rather common in neuro-ophthalmology practice, and GGT is one of the most sensitive indicators for liver function changes [ 6 ]. Moreover, it has been found that hepatic cirrhosis patients are prone to smooth pursuit eye movements (SPEM) disruption [ 35 ].…”
Section: Epidemiological Evidence and Public Health Significancementioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that palsies of the 3rd, 4th, and 6th cranial nerve are rather common in neuro-ophthalmology practice, and GGT is one of the most sensitive indicators for liver function changes [ 6 ]. Moreover, it has been found that hepatic cirrhosis patients are prone to smooth pursuit eye movements (SPEM) disruption [ 35 ].…”
Section: Epidemiological Evidence and Public Health Significancementioning
confidence: 99%
“…In recent years, the video electro-oculography (VOG) technique designed for early detection of dysfunctional cognitive/motor abilities in Parkinson’s, Alzheimer’s disease or multiple sclerosis has also been tested in diagnosing minimal hepatic encephalopathy (MHE), the earliest form of hepatic encephalopathy commonly found in liver cirrhosis patients [ 35 , 171 173 ]. The results showed that MHE patients have longer latencies and worse performance in most eye movement tests, of which the latency of reflexive saccades in vertical antisaccades test and the vertical version of the memory-guided saccades test [ 35 ]. The underlying mechanism relates to impaired mental processing speed and attention [ 35 ].…”
Section: Clinical Links and Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation